2002
DOI: 10.1046/j.1365-2672.2002.01732.x
|View full text |Cite
|
Sign up to set email alerts
|

Peracetic acid as an alternative wastewater disinfectant to chlorine dioxide

Abstract: Aims: The aim of this study was to compare the efficiency of peracetic acid with that of chlorine dioxide in the disinfection of wastewater from a sewage treatment plant (serving about 650 000 inhabitants) that has been using peracetic acid as a disinfectant since 1998. Methods and Results: A total of 23 samplings were made, each consisting of three samples: from secondary effluent, effluent disinfected with 2 mg l−1 of peracetic acid and effluent disinfected with 2·2 mg l−1 of chlorine dioxide (contact time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(18 citation statements)
references
References 18 publications
1
16
0
1
Order By: Relevance
“…Chlorine dioxide has been reported to be either more effective than PAA [126] or similar [130] in terms of disinfection efficiency against typical bacterial indicators. Contradicting results were obtained by De Luca et al [131], who concluded PAA to be preferable to chlorine dioxide, since it was less affected by organic matter, had a better disinfection efficiency, and was more economical and easier to apply.…”
Section: Reactions In Aqueous Media: Disinfection and Oxidation Mechamentioning
confidence: 99%
“…Chlorine dioxide has been reported to be either more effective than PAA [126] or similar [130] in terms of disinfection efficiency against typical bacterial indicators. Contradicting results were obtained by De Luca et al [131], who concluded PAA to be preferable to chlorine dioxide, since it was less affected by organic matter, had a better disinfection efficiency, and was more economical and easier to apply.…”
Section: Reactions In Aqueous Media: Disinfection and Oxidation Mechamentioning
confidence: 99%
“…The results from the cluster analysis indicate that, at the concentrations used QAC(b) and iodophor-based disinfectants were similarly effective against all of the microorganisms tested, while peracetic acid-based disinfectant was only effective against the moulds. PAA has shown good disinfection efficiency against enteric bacteria in wastewaters, but viruses, bacterial spores and protozoan cysts are more resistant (Liberti and Notarnicola, 1999;Stampi et al, 2001Stampi et al, , 2002Salgot et al, 2002;Wagner et al, 2002;Veschetti et al, 2003;Koivunen and Heinonen-Tanski, 2005). In addition, peracetic acid-based disinfectant might be used for the inhibition of food borne fungi as an industrial surface disinfectant.…”
Section: Chlorinementioning
confidence: 99%
“…1.5-2 ppm of peracetic acid or 2.2 ppm of chlorine dioxide (Stampi et al, 2001(Stampi et al, , 2002.…”
Section: Discussionmentioning
confidence: 99%
“…It is active against enteric bacteria, and to a lesser degree against viruses, bacterial spores and protozoan cysts (Stampi et al, 2001(Stampi et al, , 2002Veschetti et al, 2003;Koivunen and Heinonen-Tanski, 2005b). Peracetic acid is easy to use, has no quenching requirement (Kitis, 2004) and does not generate any significant amounts of toxic or mutagenic DBPs, or chemical residues in effluents (Monarca et al, 2000;Veschetti et al, 2003;Crebelli et al, 2005;Koivunen and Heinonen-Tanski, 2005b).…”
Section: Introductionmentioning
confidence: 99%